948 Traumatic Native Hip Dislocation Without Associated Fracture: A Case Series of 13 Patients Over 9 Years. (19th August 2022) - Varma, J; Jones, C; Fowler, T; Chesser, T; Ward, A; Acharya, M
Abstract: Aim: Traumatic native hip dislocation (NHD) is rarely without an associated fracture or due to low energy trauma. Posterior dislocation is the most common pattern of hip dislocation. In most cases, closed reduction is successful, but occasionally open reduction is required to achieve appropriate reduction. The aim of our study was to present the 9-year experience from our institution of this rare injury pattern and to comment on how our experience correlates with the current literature. Method: This is a retrospective case series of all adult patients (> 16 years old) with a traumatic NHD without fracture presented and/or treated at our institution, between the 1 st of January 2012 and 22 nd June 2021. Results: Thirteen cases of traumatic NHD were identified (38.4% female). The mean age was 26.5 years. Typically, younger patients were involved in lower energy injuries. The direction of hip dislocation was posterior in 10 cases. Associated injuries were seen in 3 patients. 12 cases underwent successful closed reduction, and 1 case was operatively managed. 3 cases had a previous hip pathology including femoroacetabular impingement, cam lesion and childhood slipped upper femoral epiphysis. Conclusions: Traumatic NHD without associated fracture is a rare injury pattern, most commonly occurring in patients under the age of thirty. A target of 6 hours for reduction should be employed as this will reduce the risk of AVN in those who have not permanently damaged the vessels at the time of injury.